2017
DOI: 10.1186/s13023-017-0734-x
|View full text |Cite
|
Sign up to set email alerts
|

Receptor of ghrelin is expressed in cutaneous neurofibromas of individuals with neurofibromatosis 1

Abstract: BackgroundMultiple cutaneous neurofibromas are a hallmark of neurofibromatosis 1 (NF1). They begin to appear during puberty and increase in number and volume during pregnancy, suggesting a hormonal influence. Ghrelin is a hormone that acts via growth hormone secretagogue receptor (GHS-R), which is overexpressed in many neoplasms and is involved in tumorigenesis. We aimed to investigate GHS-R expression in NF1 cutaneous neurofibromas and its relationship with tumors volume, and patient’s age and gender.ResultsS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…For the S100 and leptin immunohistochemistry investigation, larger lesions, three to five morphologically representative cores (1.1 mm diameter) were included in tissue microarray blocks constructed as previously described . For small lesions, whole specimens were evaluated after inclusion in tissue macroarrays, which were constructed as described previously . For CD34 antibody, the whole specimens were investigated.…”
Section: Methodsmentioning
confidence: 99%
“…For the S100 and leptin immunohistochemistry investigation, larger lesions, three to five morphologically representative cores (1.1 mm diameter) were included in tissue microarray blocks constructed as previously described . For small lesions, whole specimens were evaluated after inclusion in tissue macroarrays, which were constructed as described previously . For CD34 antibody, the whole specimens were investigated.…”
Section: Methodsmentioning
confidence: 99%
“…GHSR1a is highly expressed in the hypothalamus and pituitary, but it is weakly expressed in the pancreas, spleen, kidney, and adrenal gland [ 83 , 84 , 85 ]. Although it has been previously reported that GHSR1a is not detected in mouse and human skin by quantitative RT-PCR [ 84 , 85 ], immunohistochemical examination demonstrated that GHSR1a was present in skin epidermis and annexes surrounding neurofibromas [ 86 ]. In skin wounds, granulation tissues are positive for GHSR1a in the dermis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…No significant correlations were found between ghrelin and GHS-R1a expression (88). Likewise, tumor GHSR expression was associated with higher tumor size in patients with neurofibromatosis 1 (89). Like RCC, this is another example of dominance of in-vitro local findings in the summary clinical role of ghrelin in a type of human cancer.…”
Section: Other Cancersmentioning
confidence: 99%